Performance, Physiological and Blood Profile of Kalawad Bucks fed Brachiaria Ruziziensis or Panicum maximum - Sanusi, Ganiyu O.; Olalere, Johnson O.; Toviesi, Dedeanu P.; Ayomiposi, Akinneye K.; Oderinwale, Olatunde A.; Taiwo, Seyi F.; Oluwatosin, Bamidele O. (Syiah Kuala University, 2025)
This study evaluated growth performance, physiological parameters and blood profile of crosses between Kalahari Red bucks and West African Dwarf does (KalaWAD) fed ruzi (Brachiaria ruziziensis) and/or guinea grass (Panicum maximum). Twelve (12) KalaWAD bucks were randomly allotted to three dietary treatments: Panicum maximum (PM), Brachiaria ruziziensis (BR) and 1:1 mixture of Panicum maximum and Brachiaria ruziziensis (PMBR) for 84 days. The data obtained were subjected to one-way analysis of variance using a completely randomized design. Crude protein (p0.05) and ether extract (p0.05) were in the range from 5.68-7.35% and 0.82-1.11% respectively. Crude fibre (p0.05) and ash content (p0.05) were highest in PM with values of 37.75% and 11.38% respectively. PMBR had a dry matter content of 90.93% while the highest value of nitrogen free extract (55.19%) was observed in BR. PM recorded the highest weight gain of 2.75 kg and feed conversion ratio of 14.19. The daily weight gain of crosses fed PM, BR and PMBR were 49.11 gday-1 , 35.00 gday-1 and 34. gday-1 respectively. The feed conversion ratio was in the range between 14.19 and 20.64. Physiological parameters were significantly (p0.05) influenced with highest values in heart (88.121.02 beat/minutes) and pulse rate (72.280.61 beat/minutes) of bucks fed with PM while highest value of rectal temperature was observed to be 38.58oC in BR. Haematological parameters (p0.05) of the bucks fed with PM, BR and PMBR were within the normal range. Total bilirubin, Zinc and Sodium were significantly (p0.05) influenced by the diets. The study concluded that the experimental diets promoted growth rate, haematological and physiological parameters which resulted in healthy and better performance as observed in KalaWAD bucks fed with PM.